The South at the End of the Twentieth Century
XIII, 270 p.
Keywords: This collection is concerned with revisiting and redefining the political economy - both empirical and theoretical - of 'foreign policy' in the South as we approach the twenty-first century: the position of post-colonial states and societies in the post-Bretton Woods and Cold War world. With a focus on Africa, Asia, the Caribbean and Latin America, this collection comparatively examines the impact of changing political and economic structures upon policy-makers and civil societies in the South.